Evaluasi Pembelajaran: Pemanfaatan hasil evaluasi untuk perbaikan pembelajaran - Maghfiroh, Choirunnisa Maulidia (Maliki Interdisciplinary Journal, 2025)
Learning evaluation is an important part of education that assesses the effectiveness of teaching and the achievement of learners. Evaluation results are used not only to assess academic achievement, but also to inform improvements to learning methods and strategies. This article discusses how evaluation results can be used to improve learning quality through systematic reflection, data analysis and follow-up. There are various forms of assessment, such as formative, summative, diagnostic, process and product, each of which plays a role in understanding learner development. Reflecting on evaluation results helps educators to identify the strengths and weaknesses of learning and to develop appropriate action plans. Additionally, follow-up through remedial and enrichment programmes is a strategic step to overcome learning obstacles and optimise students’ potential. By utilising evaluation results appropriately, educators can create a more effective and sustainable learning environment. This article aims to provide a broader understanding of the importance of evaluation as a tool for improving education.